Four-in-One: A Comprehensive Checklist for the Assessment of Pain, Undersedation, Iatrogenic Withdrawal and Delirium in the PICU: A Delphi Study - van Dijk, Monique; Ista, Erwin (Frontiers in Pediatrics, 2022)
Objectives: Children’s pain, undersedation, iatrogenic withdrawal syndrome and delirium often have overlapping symptoms, which makes it difficult to decide why a child in the PICU is not comfortable. Validated assessment tools for these conditions are available, but regular assessment with multiple instruments may be too time-consuming. Therefore, we aimed to develop a new holistic instrument – the mosaIC checklist – that incorporates the assessment of the four conditions. Materials and methods: We conducted a two-rounds international Delphi study among experts working in PICUs worldwide to find cues that in combination or separately are relevant for the four conditions. Results: In the first Delphi round, thirty-eight of the 48 enrolled participants (79%) completed a questionnaire; in the second round 32 of 48 (67%). Eventually, forty-six cues in eight categories (e.g. facial, vocal/verbal, body movements, sleep /behavioral state, posture/muscle tone, agitation, physiological and contextual) were found relevant. Thirty-three (72%) were considered relevant for pain, 24 for undersedation (52%), 35 for iatrogenic withdrawal syndrome (76%) and 28 (61%) for pediatric delirium. Thirteen cues (28%) were considered relevant for all four conditions; eleven s (24%) for only one condition. Conclusions: This Delphi study is the first step in developing a 4-in-1 comprehensive checklist to assess pain, undersedation, iatrogenic withdrawal syndrome and delirium in a holistic manner. Further validation is needed before the checklist can be applied in practice. Application of the mosaIC checklist could help determine what condition is most likely to cause a child’s discomfort – and at the same time help reduce the PICU staff’s registration burden.